2021
DOI: 10.1111/tmi.13711
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological burden of Chikungunya fever in Brazil, 2016 and 2017

Abstract: Chikungunya fever (CHIKF) is a disease caused by the CHIK virus, which belongs to the family Togaviridae, genus Alphavirus [1]. Its main form of transmission is through bites from mosquitoes belonging to the species Aedes aegypti and Aedes albopictus, which results in its classification as an arboviral disease. Other, less frequent forms of transmission have been reported in the literature, such as blood transfusion or vertical transmission from mother to foetus during pregnancy [2].CHIKF is an infectious and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…In 2017, these values were 87.59, 0.12/100,000, and 0.14%, respectively. In 2016, Brazil lost 77,422.61 DALYs or 0.3757/1000 people, and in 2017, 59,307.59, or 0.2856/1000 people [ 81 ]. The official national surveillance systems (SINAN and SIM) reported 552,023 chikungunya cases between 2014 and 2017, with 403 deaths and a lethality rate (LR) of 0.7/1000 cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2017, these values were 87.59, 0.12/100,000, and 0.14%, respectively. In 2016, Brazil lost 77,422.61 DALYs or 0.3757/1000 people, and in 2017, 59,307.59, or 0.2856/1000 people [ 81 ]. The official national surveillance systems (SINAN and SIM) reported 552,023 chikungunya cases between 2014 and 2017, with 403 deaths and a lethality rate (LR) of 0.7/1000 cases.…”
Section: Resultsmentioning
confidence: 99%
“…About 13.66% of cases may evolve into CCA [ 84 ]. Several articles evaluated the risks of chronicity and found that older age [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[31][32][33] The fatality rate of CHIKV infection is low and is reported to be 0.1% on La Reunion; however, other publications have reported up to 5%. 34,35 Fatality mainly affects the elderly, neonates and young children, pregnant women and patients with co-morbidities. 36,37 Treatment of patients is limited to symptomatic therapy using analgesics and/or nonsteroidal anti-inflammatory drugs for pain and fever relief.…”
Section: Chikungunya Virusmentioning
confidence: 99%